2021
DOI: 10.1002/cli2.11
|View full text |Cite
|
Sign up to set email alerts
|

Identifying local‐scale meteorological conditions favorable to large fires in Brazil

Abstract: This study aims to investigate local-scale meteorological conditions associated with large fires in Brazil during recent decades. We assess whether there are large fire types with preceding predictors. Our results show that large fires, defined with a threshold of a daily burned area >95th percentile of the historical record, mainly occur in August and September in Brazil, and Amazônia and Cerrado experience much higher numbers of large fires than the other biomes. There are two large fire types that have robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…In line with this finding, Li et al (2022) indicated that drought-driven large fires accounted for <30% of the total large fires registered in the Brazilian Amazon from 2001 to 2015.…”
Section: Spatial Extent Of Anomalies (A) (B) (C)supporting
confidence: 76%
See 1 more Smart Citation
“…In line with this finding, Li et al (2022) indicated that drought-driven large fires accounted for <30% of the total large fires registered in the Brazilian Amazon from 2001 to 2015.…”
Section: Spatial Extent Of Anomalies (A) (B) (C)supporting
confidence: 76%
“…In other words, the majority of anomalously high fire occurrences in the Amazon since 2003 may not have been influenced by droughts. In line with this finding, Li et al (2022) indicated that drought‐driven large fires accounted for <30% of the total large fires registered in the Brazilian Amazon from 2001 to 2015.…”
Section: Discussionmentioning
confidence: 64%
“…195 Fires in Cerrado have been shown to be linked with meteorological conditions, in particular rainfall and temperature. 196,197 For instance, the Daily Severity Rating (DSR in short, an extension of the Canadian Forest Fire Weather Index System) explains 71% of the interannual variability of burned area in Cerrado. 198 Here, we show further evidence for the Cerrado's fire seasons (defined here as August-October) from 2001 to 2019 of a link between CDHW conditions with fire activity over four Cerrado ecoregions (Figure 5): Bico do Papagaio, Araguaia Tocantins, Bananal, and Alto Parnaíba.…”
Section: The Pantanal Wetlandsmentioning
confidence: 99%
“…This fire‐prone biome sees high fire activity every year as the largest contributor to Brazil's annual burned area and a major fire hotspot worldwide 195 . Fires in Cerrado have been shown to be linked with meteorological conditions, in particular rainfall and temperature 196,197 . For instance, the Daily Severity Rating (DSR in short, an extension of the Canadian Forest Fire Weather Index System) explains 71% of the interannual variability of burned area in Cerrado 198 .…”
Section: Impacts Of Cdhw Events On the Environment And Society: Early...mentioning
confidence: 99%
“…Thus, developments in rainfall modelling and predictability can pull through to actionable advice. Li et al (2021) show how predictability of events such as fires may be improved using observed links to meteorological conditions which themselves can be predicted better than the impacts directly. Example services supported by CSSP Brazil include early warning of the annual maximum river height in Manaus (Chevuturi et al, 2021) and seasonal warnings of fire risk in Brazil's Protected Areas (Anderson et al, 2021)-an activity which has now produced multiple warnings and is transitioning to routine production.…”
Section: Science For Adaptationmentioning
confidence: 99%